2019
DOI: 10.3390/app9101985
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Automatic and Manual Calibration of an Office Building Energy Model

Abstract: Featured Application: This work could contribute to evidence strengths and weaknesses of manual and automatic calibration of building dynamic simulation models leading at improving the quality of building retrofit solutions investigation.Abstract: Energy reduction can benefit from the improvement of energy efficiency in buildings. For this purpose, simulation models can be used both as diagnostic and prognostic tools, reproducing the behaviour of the real building as accurately as possible. High modelling accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Papers [1][2][3] are focused on simulation techniques for the evaluation of the energy performance of buildings. For example, Sabina Jordan [1] and her colleagues conducted a parametric study of the influence of the occupant behavior on the energy performance of an office building provided with radiant ceiling panels for heating and cooling.…”
Section: Energy Efficiency In Buildings and Innovative Materials For mentioning
confidence: 99%
See 1 more Smart Citation
“…Papers [1][2][3] are focused on simulation techniques for the evaluation of the energy performance of buildings. For example, Sabina Jordan [1] and her colleagues conducted a parametric study of the influence of the occupant behavior on the energy performance of an office building provided with radiant ceiling panels for heating and cooling.…”
Section: Energy Efficiency In Buildings and Innovative Materials For mentioning
confidence: 99%
“…They used TRNSYS, and they concluded that specific human activities influence the annual energy use a small amount and their effects often counteract. Cristina Cornaro and her colleagues [2] made a comparison of two different procedures for energy dynamic model calibration-manual and automatic-using the IDA ICE tool. They built up an automatic calibration procedure and compared it to standard manual calibration for an office building located in Rome, Italy.…”
Section: Energy Efficiency In Buildings and Innovative Materials For mentioning
confidence: 99%
“…For this reason, the process is often streamlined by the modeler's experience [6], or, in a more objective way, by a preliminary sensitivity analysis identifying the most influential parameters. In an automatic calibration, the analyst identifies the uncertain parameters and their variation, while an automated process based on mathematical or statistical methods is used to perform the calibration [7]. Optimization methods are often adopted, so that one or more objective functions are set and the solutions of the calibration problem correspond to the local minima obtained by an optimization program coupled with the BES tool.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hong, Kim, Jeong, Lee and Ji [33] calibrated a school building using a genetic algorithm to find global optimal solutions; and Sanyal, New and Edwards [34] automatically calibrated a BEM using trained machine agents from a large set of parametric simulations through machine learning, exploiting supercomputing resources. A general disadvantage of optimization methods is the dependency of the calibration procedure on the optimization settings [35].Difficulties may arise in selecting optimization hyperparameters settings, which can lead to local minima problems [32].…”
Section: Introductionmentioning
confidence: 99%